HUBUNGAN ANTARA DIAMETER POHON DAN PRODUKSI GETAH DALAM PENYADAPAN GETAH AGATHIS spp - Ishak Sumantri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This paper presents the resull an invaligation of the relationship between tree diameter and copal production in the Agathis spp tapping. Copal lappings were done using slanted and horizontal tapping patterns on the Agathis trees having diameter between 24 and 40 cm with the age of 20 years.The results of data analysis are as follows :1. At the even age Agathis trees, there was no relationship between tree diameter and copal production.2.Viewing from the coefficient of determination, the contribution of slanted tapping pallern was 12% and horizontal tapping pattern was 1%. Other factors that may affect copal production are the color of bark and leaf, crown size and the direction of resin canal.3.Better relationship between diameter and copal production may be obtained if the size of tapping quare is proportional to tree diameter/perimeter.4.Further investigation, by including other variables, is suggested in order to formulatete better relationship.